2015
DOI: 10.18006/2015.3(3).246.252
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate stability of four soils as evaluated by different indices

Abstract: KEYWORDS Aggregate stabilityGeometric mean-weight Diameter Mean-weight diameter ABSTRAC TIn present study, aggregate stability of four soils viz Entisol, Ultisol and t wo Inceptisols were evaluated usin g different indices. Soil samples from the depth of 0 -25cm were collected from cultivated and adjacent fallow lands at the four different sites located, at Nsukka area of southeastern, Nigeria. The soil samples were air-dried at room temperature and then were separated into five aggregate fractions i.e. 5 -2mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In addition, positive correlations were obtained between MWD and soil OC (r=0.66; P<0.05) and MB-C (r=0.64; P<0.05). Different experiments have demonstrated that aggregate stability increases when clay and organic matter accumulation increase, confirming the role of these soil properties in soil aggregation (Norton et al, 2006;Nweke and Nnabude, 2015). Aziz and Karim (2016) monitored in the climatological region of Iraqi Kurdistan region with different uses of agricultural land certain soil properties in relation to soil aggregates.…”
Section: Dry Mean Weight Diametermentioning
confidence: 74%
“…In addition, positive correlations were obtained between MWD and soil OC (r=0.66; P<0.05) and MB-C (r=0.64; P<0.05). Different experiments have demonstrated that aggregate stability increases when clay and organic matter accumulation increase, confirming the role of these soil properties in soil aggregation (Norton et al, 2006;Nweke and Nnabude, 2015). Aziz and Karim (2016) monitored in the climatological region of Iraqi Kurdistan region with different uses of agricultural land certain soil properties in relation to soil aggregates.…”
Section: Dry Mean Weight Diametermentioning
confidence: 74%